Hubungan Pengetahuan Tentang Makanan Berserat Dengan Kejadian Konstipasi Pada Mahasiswa Fakultas Kedokteran Universitas Malahayati Bandar Lampung - Muhammad Amar Abyan; Dwi Robbiardy Eksa; Ika Artini (Universitas Malahayati Lampung, 2021)
ABSTRACT: CORRELATION OF KNOWLEDGE ABOUT FIBER FOOD WITH CONSTIPATION IN MEDICINE FACULTY STUDENTS OF MALAHAYATI UNIVERSITY BANDAR LAMPUNG Background: Constipation can cause severe stress for sufferers because of the discomfort. Constipation is generally considered normal, but if left untreated, constipation can lead to more serious situations such as impaction (hard and dry stools) and obstruction. The average prevalence of constipation in adult patients worldwide is 16%, while in pediatric patients it is 12%. A systematic review reported that the prevalence of constipation increased at the age of 60-110 years, ie 33.5%, and was higher in the female sex.Objective: To find out the relationship between knowledge about the importance of fibrous food and the incidence of constipation in students of the Faculty of Medicine, Malahayati University, Bandar Lampung in 2020.Methods: This type of research is a quantitative, analytic survey design with a cross-sectional approach. The population of all 2016 FK students and a sample of 78 people using random sampling technique. Data collection using a questionnaire sheet. Data analysis using Chi-Square statistical test.Results: The distribution of sex frequency is mostly female as many as 96 respondents (53.93%). Constipation frequency distribution, with constipation category as many as 87 respondents (48.9%). The distribution of the frequency of knowledge about the importance of fibrous food is mostly in the unfavorable category as many as 97 respondents (54.5%).Conclusion: There is a relationship between knowledge about the importance of fiber foods with the incidence of constipation. The results of the analysis obtained a value (p-value 0.000 0.05). OR: 14,557. Keywords: Knowledge, constipation INTISARI: HUBUNGAN PENGETAHUAN TENTANG MAKANAN BERSERAT DENGAN KEJADIAN KONSTIPASI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MALAHAYATI BANDAR LAMPUNG Latar Belakang : Konstipasi dapat menimbulkan stres berat bagi penderita akibat ketidaknyamanan. Pada umumnya konstipasi dianggap sebagai hal yang biasa namun jika tidak diatasi konstipasi dapat menimbulkan situasi yang lebih serius seperti impaksi (feses menjadi keras dan kering) dan obstruksi. Prevalensi rata-rata keluhan konstipasi pada pasien dewasa di seluruh dunia adalah 16%, sedangkan pada pasien anak adalah 12%. Suatu systematic review melaporkan prevalensi konstipasi semakin meningkat pada usia 60-110 tahun yaitu 33.5%, dan lebih tinggi pada jenis kelamin perempuan.Tujuan: Diketahui hubungan antara pengetahuan tentang pentingnya makanan berserat dengan kejadian konstipasi Pada Mahasiswa Fakultas Kedokteran Universitas Malahayati Bandar Lampung Tahun 2020.Metode: Jenis penelitian kuantitatif, rancangan survey analitik dengan pendekatan cross sectional. Populasi seluruh mahasiswa FK angkatan 2016 dan sampel 78 orang dengan teknik random Sampling. Pengambilan data menggunakan lembar kuesioner. Analisis data menggunakan uji statistik Chi Square. Hasil: Distribusi frekuensi jenis kelamin, sebagian besar adalah jenis kelamin perempuan sebanyak 96 responden (53,93%). Distribusi frekuensi kejadian konstipasi, dengan kategori mengalami konstipasi sebanyak 87 responden (48,9%). Distribusi frekuensi pengetahuan tentang pentingnya makanan berserat, sebagian besar kategori kurang baik sebanyak 97 responden (54,5%). Kesimpulan : Ada hubungan antara pengetahuan tentang pentingnya makanan berserat dengan kejadian konstipasi. Hasil analisis diperoleh nilai (p-value 0,000 α 0,05). OR: 14,557. Kata Kunci : Pengetahuan, konstipasi